1997
DOI: 10.1523/jneurosci.17-12-04849.1997
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Nucleus Accumbens Dopamine Efflux During the Coolidge Effect in Male Rats

Abstract: The Coolidge effect describes the reinitiation of sexual behavior in a "sexually satiated" animal in response to a novel receptive mate. Given the role of the mesolimbic dopamine (DA) system in the initiation and maintenance of motivated behavior, microdialysis was used to monitor nucleus accumbens (NAC) DA transmission during copulation, sexual satiety, and the reinitiation of sexual behavior. In agreement with earlier reports, the presentation of an estrous female behind a screen and copulation were associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
1
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(114 citation statements)
references
References 42 publications
5
104
1
1
Order By: Relevance
“…These dopaminergic systems are involved in those mechanisms which determine satiety to food, 23 sex, 24 and drugs of abuse. 25 In all these conditions, the most important dopamine systems involved are that of the terminal fields of the prefrontal cortex, 26 and that of the nucleus accumbens, 27 both originating from neurons located in the ventral tegmental area of the midbrain.…”
Section: Receptor Familymentioning
confidence: 99%
“…These dopaminergic systems are involved in those mechanisms which determine satiety to food, 23 sex, 24 and drugs of abuse. 25 In all these conditions, the most important dopamine systems involved are that of the terminal fields of the prefrontal cortex, 26 and that of the nucleus accumbens, 27 both originating from neurons located in the ventral tegmental area of the midbrain.…”
Section: Receptor Familymentioning
confidence: 99%
“…These neurochemical data may explain our previous finding that withdrawal from an ED schedule of D-amph decreased selectively the preparatory components of sexual behavior in sexually experienced male rats . Previous in vivo microdialysis studies by our group have reported an immediate increase in DA levels in the NAc of sexually experienced male rats in the presence of an inaccessible receptive female (Fiorino et al, 1997;Fiorino and Phillips, 1999), which suggests that activity within the mesocorticolimbic DA pathway may be especially important for the initiation of motivated behavior. Furthermore, it is this rapid rise in DA efflux in the NAc that may be especially sensitive to the disruptive effects of withdrawal from extended exposure to psychostimulant drugs.…”
Section: Discussionmentioning
confidence: 71%
“…This mesocorticolimbic dopamine (DA) pathway plays a critical role in many aspects of reward, including motivational states triggered by natural incentive stimuli (eg, food, sex, and social interaction) or pharmacological stimuli that can maintain drug self-administration (Everitt et al, 1999;Koob et al, 1998;Wise, 1998). In vivo microdialysis studies in rats report increased DA efflux in the NAc during preparatory and consummatory phases of feeding and sexual behaviors (Phillips et al, 1993;Wilson et al, 1995;Fiorino et al, 1997;Ahn and Phillips, 1999). Furthermore, virtually all drugs of abuse increase DA transmission in the NAc, which partly mediates their rewarding effects (Koob et al, 1998;Wise, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…NAcS involvement in performance of sexual behavior Previous studies have investigated only four aspects of NAcS activity during sexual behavior: c-fos expression (Robertson et al, 1991;Olivier et al, 2007), tonic dopamine release (Damsma et al, 1992;Fiorino et al, 1997;Lorrain et al, 1999), phasic dopamine release (Robinson et al, 2001(Robinson et al, , 2002, and local field potentials (LFPs) (Guevara et al, 2008). To our knowledge, no previous studies have investigated the male rat NAcS neuronal activity during sexual behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that dopamine was also released in the NAc during copulation (Pfaus et al, 1990;Damsma et al, 1992;Fiorino et al, 1997). Dopamine release in the NAc is rewarding (Wise, 2004) and was much higher during copulation than during female presentation without physical contact (Pfaus et al, 1990;Damsma et al, 1992;Fiorino et al, 1997).…”
Section: Nacs Involvement In Reward-related Functions Of Sexual Behaviormentioning
confidence: 95%